2023
DOI: 10.1002/adem.202300164
|View full text |Cite
|
Sign up to set email alerts
|

Spinodal Decomposition of B2‐phase and Formation of Cr‐Rich Nano‐precipitates in AlCoCrFeNi2.1 Eutectic High‐Entropy Alloy

Abstract: Herein, the occurrence of a B2‐phase separation and formation of Cr‐rich nano‐precipitates during the solidification process of AlCoCrFeNi2.1 eutectic high‐entropy alloy is addressed. Toward this end, various advanced characterizations, including high‐resolution transmission electron microscopy and atom probe tomography combined with thermodynamic calculations, are employed. The as‐solidified microstructure is composed of face‐centered cubic (FCC) dendrites and interdendritic regions consisting of a eutectic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This microstructure results from the instability of the solidification front and significant elemental partitioning, which give rise to the dendritic and interdendritic regions. [ 42,43 ] Based on previous research concerning the mentioned microstructure, it has been revealed that the dendrites are enriched in Fe, whereas the interdendritic regions are enriched in Mn and Co. Additionally, other elements show a uniform distribution. Therefore, the distinctions between the dendritic and interdendritic areas are solely related to the local variation of the chemical composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This microstructure results from the instability of the solidification front and significant elemental partitioning, which give rise to the dendritic and interdendritic regions. [ 42,43 ] Based on previous research concerning the mentioned microstructure, it has been revealed that the dendrites are enriched in Fe, whereas the interdendritic regions are enriched in Mn and Co. Additionally, other elements show a uniform distribution. Therefore, the distinctions between the dendritic and interdendritic areas are solely related to the local variation of the chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Substantial research endeavors [4][5][6] have been directed toward addressing this inverse relationship by advancing materials, including ultrahighstrength steels, aluminum alloys, and more recently, high-entropy alloys (HEAs).HEAs are a new rising category of advanced materials consisting of five or more elements, with atomic percentages ranging from 5% to 35%. [7,8] The concept of incorporating equal proportions of constituent elements within the alloy system has given rise to well-known equiatomic HEAs like CoCrMnFeNi, which have demonstrated exceptional mechanical properties at room temperature. [9] Among the most promising groups are singlephase FCC HEAs, which generally exhibit acceptable ductility yet mediocre yield strength due to their composition of a single austenite phase.…”
mentioning
confidence: 99%
“…At high strain rates, the velocity of dislocations in the alloy will increase. Furthermore, according to Equation (7), it can be inferred that higher dislocation velocities result in the generation of larger shear stresses, leading to a positive correlation between the work hardening rate of the alloy and the strain rate. Additionally, it is observed that in specimens with larger grain sizes, the enhancement in the alloy's performance and deformation strengthening capability due to high strain rates is more pronounced.…”
Section: Strain Hardening Behaviorsmentioning
confidence: 99%
“…In FeMnCoCr-based high-entropy alloys, the incorporation of aluminum (Al) atoms can be strategically employed to fine-tune the stacking fault energy of the alloy system, placing it within an optimal range. This adjustment facilitates the activation of both TRIP and TWIP effects, consequently enhancing the alloy's work-hardening capability and overall mechanical performance [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The transition may be attributed to an abrupt sharpening of the crack radius, possibly due to stress concentration at the Cr-rich precipitates and multiaxial stress condition locally [30][31][32]. Cr-rich nanoprecipitates are reported to form in the B2 phase of AlCoCrFeNi 2.1 systems as a result of spinodal decomposition driven by compositional modulation [11,33,34]. Nano-precipitates may contribute to the strengthening of an alloy by acting as dislocation inhibitors as well as dislocation generators at high stresses [35].…”
Section: Phase-specific Bending Response Of the Microcantileversmentioning
confidence: 99%